SERUM OSTEOCALCIN LEVELS IN POSTMENOPAUSAL OSTEOPOROSIS WOMEN – A CROSS SECTIONAL STUDY. - DR. B.K. JAIN; DR. SMITA S. PATNE; DR. MANINDER BINDRA (International Journal of Pharma and Bio Sciences, 2013)
Background: Increase in health care facilities increased life expectancy resulted in increase in number of older population worldwide. India had the second number of elderly (60+) population in the world with 3.3 million in 1971 to 7.66 million in 2001 and as high as 17 millions in 2011 with 49.3% males and 50.7% females. 1 out of 3 females in India suffers from osteoporosis, making India one of the largest affected countries in the world.Materials and methods: for this study we evaluated serum osteocalcin as marker for osteoporosis in 45 newly diagnosed postmenopausal osteoporotic women and in 56 age matched control group, who are not suffering from osteoporosis.Results: we observed significantly higher levels of serum osteocalcin in study population 21.4 + 3.8 ng/ml when compared to control group 18.9 + 4.6 ng/ml (P<0.01).Conclusion: from this study we observed osteocalcin as beast marker for bone turnover in osteoporosis, hence also can be used as marker for diagnostic and prognosis marker in PMO (post menopausal osteoporosis)